2018
DOI: 10.1111/cge.13141
|View full text |Cite
|
Sign up to set email alerts
|

Common variants in DLG1 locus are associated with non‐syndromic cleft lip with or without cleft palate

Abstract: Non-syndromic cleft lip with or without cleft palate (nsCL/P) is a common craniofacial anomaly with a complex and heterogeneous aetiology. Knowledge regarding specific genetic factors underlying this birth defect is still not well understood. Therefore, we conducted an independent replication analysis for the top-associated variants located within the DLG1 locus at chromosome 3q29, which was identified as a novel cleft-susceptibility locus in our genome-wide association study (GWAS). Mega-analysis of the poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 51 publications
1
41
4
Order By: Relevance
“…The present study was designed similar to our previous cleft association studies (Gaczkowska et al, ; Mostowska et al, ). Data on common single nucleotide polymorphisms (SNPs) located within the PAX7 locus were retrieved from our GWAS for nsCL/P (unpublished results), which was performed with the use of the HumanOmniExpressExome v1 array (Illumina).…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…The present study was designed similar to our previous cleft association studies (Gaczkowska et al, ; Mostowska et al, ). Data on common single nucleotide polymorphisms (SNPs) located within the PAX7 locus were retrieved from our GWAS for nsCL/P (unpublished results), which was performed with the use of the HumanOmniExpressExome v1 array (Illumina).…”
Section: Methodsmentioning
confidence: 93%
“…Statistical methods are described elsewhere (Gaczkowska et al, ; Mostowska et al, ). Briefly, statistical analyses were conducted separately using data from GWAS and replication cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Orofacial clefts (OFCs) such as cleft lip (CL), cleft palate (CP), and cleft lip with cleft palate (CLP) are among the most common birth defects in humans with prevalence between 1 in 500 and 1 in 2,500 live births (Tessier, 1976; Mossey et al, 2009). Extensive recent studies identified common nucleotide variants associated with orofacial clefts, such as 1p22.1, 2p24.2, 3q29, 8q24.21, 10q25.3, 12q12, 16p13.3, 17q22, 17q23, 19q13, and 20q12 (Birnbaum et al, 2009; Grant et al, 2009; Beaty et al, 2010; Mangold et al, 2009; Wolf et al, 2015; Leslie et al, 2016a,b; Mostowska et al, 2018). However, the role of rare genetic variation in OFCs is still underway.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of this paper is as follows: after introducing the ordinal GAMuT method using the KDC framework (Gretton et al, 2008; Székely et al, 2007; Kosorok, 2009; Zhang et al, 2012; Hua and Ghosh, 2015), we present simulation work to show that leveraging family history information via ordinal categorical variables can improve power in rare-variant association tests compared to standard dichotomous modeling of disease phenotypes that ignore such information, like the burden test (Li and Leal, 2008) and Sequence Kernel Association Test (SKAT) (Wu et al, 2011). Finally, we apply ordinal GAMuT to rare and less-common variant data from a genome-wide study of craniofacial defects (Leslie et al, 2016a,b; Mostowska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%